Pengaruh Pengetahuan Akuntansi Terhadap Kemauan Pelaku Umkm Membuat Laporan Keuangan - -, Kurniawan (CV. ITTC INDONESIA, 2024)
Micro, Small, and Medium Enterprises (UMKM) are vital to Indonesia's economy, contributing significantly to GDP and employment. However, many UMKM struggle with financial management, especially in accounting and financial reporting, due to a lack of accounting knowledge. Adequate accounting knowledge is essential for UMKM to create reliable financial reports that can help with decision-making, financial planning, and accessing financing. This research aims to assess the impact of accounting knowledge on UMKM entrepreneurs' willingness to create financial reports, identify challenges they face in implementing accounting practices, and recommend strategies to improve accounting knowledge. Past studies have shown that good accounting knowledge leads to better financial performance for UMKM. Challenges in implementing accounting practices include low education levels and limited resources for training. Providing digital accounting training is recommended to enhance UMKM entrepreneurs' ability to produce accurate and efficient financial statements.